OP42 Mental Disorders Across the Adult Lifecourse and Future Coronary Heart Disease: Evidence for General Susceptibility. (10th September 2013) - Gale, C R; Batty, G D; Osborn, D P J; Tynelius, P; Rasmussen, F
Abstract : Background: Depression, anxiety, and psychotic disorders have been associated with an increased risk of developing coronary heart disease (CHD). The underlying mechanisms are uncertain. It is unclear whether the association between mental health and risk of CHD is present across a wider range of mental disorders, and whether it varies according to the chronicity of the disorder. We used data on over a million Swedish men who underwent psychiatric and medical assessment in early adulthood and were followed up for hospital admission for mental disorder and CHD. Our first objective was to investigate whether the risks of incident CHD associated with a range of mental disorders diagnosed in early adulthood were similar to those associated with subsequent hospital admission for these disorders. Our second objective was to examine the extent to which risk factors measured in early adulthood (blood pressure, body mass index (BMI), smoking, alcohol intake and intelligence) together with socioeconomic circumstances in childhood or later adult life, explained these associations. Methods: Participants were 1, 095, 249 Swedish men conscripted for military service at a mean age of 18.3 years. Schizophrenia, other non-affective psychotic disorders, bipolar disorders, depressive disorders, neurotic and adjustment disorders, personality disorders, alcohol-related and other substances use disorders were assessed by psychiatric interview on conscription and data on hospital admissions for these mental disorders and for CHD (fatal and non-fatal) were obtained from national registers during a mean follow-up period of 22.6 years. Results: Increased risk of incident CHD was evident across the range of mental disorders whether diagnosed at conscription or on later hospital admission. Age-adjusted HRs (95% CIs) according to diagnoses at conscription ranged from 1.27 (1.03, 1.58) (depressive disorders) to 1.92 (1.60, 2.31) (alcohol-related disorders). The equivalent figures according to diagnoses during hospital admission were higher, ranging from 1.49 (1.22, 1.79) (schizophrenia) to 2.87 (2.58, 3.20) (other substance use disorders). Associations were little changed by adjustment for early-life socioeconomic status, BMI and blood pressure, but were partially attenuated by adjustment for smoking, alcohol intake, intelligence, education and late-life socioeconomic position. Risk of CHD rose with exposure to more chronic and perhaps more severe mental disorder (p for linear trend < 0.0001). Conclusion: Increased risk of incident CHD is present across a range of mental disorders and is observable when disorders are diagnosed at a young age. Men with early onset mental disorder who subsequently require psychiatric hospital admission are at particularly high risk.